Building psychological contract: the role of leader member exchanges - Kasekende, Francis; Munene, John C.; Ntayi, Joseph M.; Ahiauzu, Augustine (Emerald Group Publishing Limited, 2016)
The purpose of this paper is to address the building blocks for psychological contract among public institutions in Uganda by investigating the mediation effect of leader-member exchanges (LMX) in the relationship between perceived environmental dynamism and psychological contract. Design/methodology/approach – The authors use structural equation modelling (AMOS) to investigate the hypotheses. Findings – LMX is a significant mediator in the association between generational work values and psychological contract and technological advancement and psychological contract among employees in public institutions in Uganda. Practical implications – At commissions and agencies level, generational work values and technological advancement seem to create better effects on employee-employer unwritten expectations and obligations when they go through LMX. This has important implications for the investment in and outcomes of these LMX endeavours from both the employer and the employee. Originality/value – The study is one of the pioneers to demonstrate that the presence of LMX reflected in the form of a dyadic relationship helps to extend the positive effects generational work values and technological advancement have on psychological contract.
Keywords: Organizational climate; Psychological contract; Generational work values; Leader-member exchanges; Public servants; Technological advancement